Vessel perforation during stent retriever thrombectomy for acute ischemic stroke: technical details and clinical outcomes. (29th September 2016) - Mokin, Maxim; Fargen, Kyle M; Primiani, Christopher T; Ren, Zeguang; Dumont, Travis M; Brasiliense, Leonardo B C; Dabus, Guilherme; Linfante, Italo; Kan, Peter; Srinivasan, Visish M; Binning, Mandy J; Gupta, Rishi; et al.
Abstract : Background: Vessel perforation during stent retriever thrombectomy is a rare complication; typically only single instances have been reported. Objective: To report on a series of patients whose stent retriever thrombectomy was complicated by intraprocedural vessel perforation and discuss its potential mechanisms, rescue treatment strategies, and clinical significance. Methods: Cases with intraprocedural vessel perforation, where a stent retriever was used either as a primary treatment approach or as a part of a direct aspiration first pass technique (ADAPT), were included in the final analysis. Clinical data, procedural details, radiographic and clinical outcomes were collected from nine participating centers. Results: Intraprocedural vessel perforation during stent retriever thrombectomy occurred in 16 (1.0%) of 1599 cases. 63% of intraprocedural perforations occurred at distal locations. Endovascular rescue techniques (most commonly, intracranial balloon occlusion for tamponade) were attempted in 50% of cases. Procedure was aborted without any rescue attempts in 44% of cases. Mortality during hospitalization and at 3 months was 56% and 63%, respectively. 25% of patients achieved good functional outcome at 3 months after the procedure. Conclusions: Intraprocedural perforations during stent retriever thrombectomy were rare, but when they occurred were associated with high mortality. Perforations most commonly occurred at distal occlusion sites and were often characterized by difficulty traversing the occlusion with a microcatheter or microwire, or while withdrawing the stent retriever. Nevertheless, 25% of patients had a favorable functional outcome, suggesting that in some patients with this complication good neurological recovery is achievable.